PERJANJIAN DALAM PERKAWINAN (SEBUAH TELAAH TERHADAP HUKUM POSITIF DI INDONESIA) - Hanafi Arief (Al-Adl : Jurnal Hukum, 2017)
The marriage agreement is a treaty governing the consequences of a marriage bond. In Indonesia, marriage agreements are allowed to be made since the enactment of the Civil Code. The subject of this marriage agreement is then reaffirmed in the Marriage Act No. 1 of 1974. The marriage agreement is part of the field of family law set out in Book I of the Civil Code (BW). The arrangement of marriage agreements is described in Chapter VII, articles 139 to 154. In general, marriage agreements apply and bind the parties  or brides in marriage. In the Marriage Law No. 1/1974, the Marriage Agreement is found in Chapter V, containing one article, namely article 29. One of the principles contained in this Act related to the marriage agreement is the right and the position of a balanced husband and wife. Each party can perform legal acts independently. The marriage agreement in article 29 is not strictly regulated, so it implicitly can be interpreted that such marriage agreements are not limited to matters of marriage property but also other matters as long as it is not contrary to religious norms, public order and morals. The essence of the Marriage Agreement set forth in the Marriage Act No. 1/ 1974 is broader than the meaning of the marriage agreement contained in the Civil Code (BW).